Is Women’s Tendency to Negotiate Safer Sex Another Opportunity for Intimate Partner Violence in Nigeria? - Sunmola, Adegbenga M. (Journal of interpersonal violence, 2021)
Husband’s controlling and domineering attitudes have been shown to contribute to women’s intimate partner violence experience in Nigeria. Some scholars have suggested that women’s safer sex negotiation may create additional opportunity for incurring partner violence. The purpose of the current study was to test the possibility that married women’s tendency to negotiate safer sex would contribute significant additional proportions of the variance in their experience of physical, sexual, and emotional violence. Using nationally representative data from a sample of married women in Nigeria (N = 19,360), three separate hierarchical regression analyses were performed to examine the contributions of husband’s controlling and domineering attitudes and tendency to negotiate safer sex to the three types of violence experience. Regression analyses revealed that women whose husbands endorsed more controlling and domineering attitudes experienced more physical, sexual, and emotional violence. Furthermore, women with higher tendency to negotiate safer sex experienced more of all the forms of violence. After accounting for the influence of husband’s controlling and domineering attitudes, regression analyses revealed that women’s tendency to negotiate safer sex accounted for significant additional contributions of the variance in physical, sexual, and emotional violence experience. The additional contributions suggest that specific interventions may be needed for improving women’s negotiation skills to reduce husband perpetrated violence risk.